Neuromarketing and Consumer Decision-Making: A Psychological Approach to Brand Perception - Heriyana, H; Hodijah, Cucu; Zulkarnaen, Teuku (Journal of Economics and Management Scienties, 2025)
This study investigates the influence of neuromarketing stimuli on consumer decision-making through the mediating roles of emotional engagement and cognitive response, with brand perception as a key outcome variable. Employing a quantitative approach and utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS, data were collected from 250 consumers in the electronics sector. The results reveal that neuromarketing stimuli significantly affect cognitive responses, which in turn strongly influence brand perception and consumer purchase decisions. While emotional engagement is also stimulated, its effect on brand perception and purchasing behavior is not statistically significant. The findings underscore the central role of cognitive mechanisms in transforming neuromarketing inputs into favorable consumer actions, particularly in high-involvement product contexts. This research contributes to the growing body of knowledge on consumer neuroscience and offers practical implications for marketers aiming to enhance brand strategy effectiveness through psychologically grounded approaches.